Enzalutamide‐induced severe thrombocytopenia complicated by a seizure in a 76‐year‐old man with castration‐resistant prostate cancer. Issue 1 (31st October 2018) - Murata, Masaki; Takizawa, Itsuhiro; Maruyama, Ryo; Kasahara, Takashi; Hara, Noboru; Tomita, Yoshihiko
Abstract : Introduction: Adverse events with enzalutamide widely used for men with castration‐resistant prostate cancer are of interest. Case presentation: A 76‐year‐old man developed castration‐resistant prostate cancer. He received 160 mg of enzalutamide daily. On the 13th day after treatment, severe thrombocytopenia was observed (platelet count: 1.9 × 10 4 /μL). Normal coagulation and fibrinolytic systems suggested thrombocytopenia induced by enzalutamide. Enzalutamide was withdrawn immediately, and platelet count uneventfully recovered to 7.0 × 10 4 /μL and 28.8 × 10 4 /μL 9 and 30 days after discontinuation, respectively. He restarted enzalutamide therapy without thrombocytopenia recurrence. However, 81 days after restarting enzalutamide, he experienced a seizure. There were no significant findings from brain computed tomography, which suggested that the seizure was also an enzalutamide‐associated adverse event. Conclusion: Thrombocytopenia may occur early following enzalutamide therapy, and blood analysis within 2 weeks after treatment may facilitate its management. Enzalutamide‐induced thrombocytopenia, complicated by seizure, has not been reported.